Analiza ekstraktivnih spojin v bukovih sekancih - Zule, Janja (Les (Ljubljana), 2001)
Gas chromatographic analysis of extractive compounds from beech wood chips, meant for paper production, is presented. The most important groups of wood lipids like fatty acids and sterols, as well as steryl esters and triglycerides have been identified and quantitatively evaluated. Individual representatives of these groups have been characterized, among them also substances, causing detrimental effects in paper production.
Keywords: sekanci; ekstrakti; kemijska sestava; plinska kromatografija